Seks, taśmy i statusy Facebooka. O poezji Katarzyny Fetlińskiej - Łuszczykiewicz, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article attempts to analyze the poetry of Katarzyna Fetlińska with the main stress laid upon her volume Sekstaśmy (Sex Tapes). The author tries to verify critical tracks and generalizations, introduced mostly by editorial and publishing descriptions which promote the collection. He exposes the importance of dramatic and surprisingly non-ironic themes chosen by the poet, who confronts herself with the most tragic aspects of human existence: loneliness and death. The main theme of the sketch is eroticism, sexuality and even pornographic character of her poetry, directed against metaphysically scandalous friability of interpersonal relations, human objectification and nothingness of being.